Cal Culo Der I Vadas

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

CÁLCULO DE DERIVADAS

2 1 f ( x) = 9 5 x
4
4x3 − x
1) f ( x) = x 6 − x 5 + 7 x 3 − x + 8 13)
3 4

23 x
2) (
f ( x) = 3x 4 − 5 x 2 + 4 x − 1 ) 5 14) f ( x) =
4x 2 − 9

x3 + 4x
3) f ( x) = 2 e2x
3x − 2 15) f ( x) =
x 2 −1

5x 2 − x
4) f ( x) = 16) f ( x) = Ln( x 4 − 7 x 3 + x)
(2 x + 3)2
3x 2 − 1
5) f ( x) =
(7 x 3
+5 )
3 17) f ( x) = Ln 2
x +4
x +7
2

5
18) [(
f ( x) = Ln 5 x 3 + x 2 )] 4

 x 6 + 3x 
6) f ( x) =  4 
 2 x + x − 1 
19) f ( x) = Ln 7 x 4 − x

7) (
f ( x) = 3x 4 + 2 x e 4 x ) 2
−3
20) [ (
f ( x) = Ln e 2 x x 3 + 1 )]
−3
f ( x) = 3x 4 + 2 xe 4 x
2
8) 4
ex
21) f ( x) = Ln
2x − 3
9x3 + 4x − 3
9) f ( x) =
e5 x 22) f ( x) = x 4 ⋅ Ln 3 x 2 + x( )
Ln(2 x − 5)
3
ex
10) f ( x) = 3 23) f ( x) =
x 3x + 1

11) (
f ( x) = 7 3 x 5 x 4 − 2 x 3 + 4 ) 24) (
f ( x) = log 5 6 x 3 − x 2 + 5 x )
12) f ( x) = 6 x 3 + 12 x 2 − 2 x + 7 25) f ( x) = (7 x + 1) ⋅ log x 2 − 2( )
Soluciones

1)
5
f ´( x) = 4 x − x 4 + 21x 2 − 1
5
13) f ´(x) =
[(
9 5 x ⋅ 160 x 6 − 40 x 4 ⋅ Ln9 + 12 x 2 − 1
4
) ]
4
2 4x 3 − x
[( ) ]
2 3 x ⋅ 12 x 2 − 27 Ln 2 − 4 x
2) (
f ´(x) = 60 x 3 − 50 x + 20 3 x 4 − 5 x 2 + 4 x − 1 )( ) 4 14) f ´(x) =
(4 x − 9) 2
3
2

x − 1 e (x − x − 1)
2 2x 2
3x 4 − 18 x 2 − 8 15) f ´( x) = ⋅
3) f ´( x) =
(3x −2 2
)2 e 2x
(x − 1) 2 2

32 x − 3 4 x 3 − 21x 2 + 1
4) f ´(x) = 16) f ´(x) = 4
x − 7x 3 + x
(2 x + 3) 3

26 x
5) f ´( x) =
(7 x 3
+5 ) (49 x + 441x
2 4 2
− 10 x ) 17) f ´( x) = 4
3x + 11x 2 − 4
(x + 7 ) 2 2

18)
60 x + 8
f ´( x) = 2
 x + 3x  20 x + 25 x − 30 x − 90 x − 15
6 4 9 6 5 4 5x + x
6) f ´( x) =  4  ⋅ 28 x 3 − 1
 2x + x −1  2x 4 + x −1
2
( ) 19) f ´(x) =
14 x 4 − 2 x
7) (
f ´(x) = 24 x 5 + 12 x 3 + 16 x 2 + 2 e 4 x ) 2
−3
2 x 3 + 3x 2 + 2
20) f ´(x) =
x 3 +1
8) f ´( x) = 12 x 3 + e 4 x
2
−3
(16 x 2
+2 ) 21) f ´( x) =
8 x 4 − 12 x 3 − 2
2x − 3
6x 4 + x 3
9) f ´(x) =
− 45 x 3 + 27 x 2 − 20 x + 19 22) f ´(x) = 4 x Ln 3x + x +
3
( 2

3x + 1
)
e 5x
6 x + 2 − (6 x − 15)Ln(2 x − 5)
f ´( x) =
3e x x 3 − 1
3
( ) 23) f ´(x) =
10)
x4 (2 x − 5)(3x + 1)2
11) [ (
f ´( x) = 7 3 x 3Ln7 5 x 4 − 2 x 3 + 4 + 20 x 3 − 6 x 2 ) ] f ´(x) =
18 x 2 − 2 x + 5
( )
24)
9 x 2 + 12 x − 1 6 x 3 − x 2 + 5 x ⋅ Ln5
12) f ´( x) =
14 x 2 + 2 x
6 x 3 + 12 x 2 − 2 x + 7 (
f ´( x) = 7 ⋅ log x 2 − 2 + )
( )
25)
x 2 − 2 ⋅ Ln10

You might also like